Peranan Dosen dalam Meningkatkan Interaksi Sosial Mahasiswa dalam Proses Pembelajaran Sosiologi Pendidikan (Studi Multi Situs di IAIN Tulungagung dan IAIN Kediri) - Binti Maunah; Mirna Wahyu Agustina (Institut Agama Islam Negeri (IAIN) Tulungagung, 2019)
Reality shows that there are problems in education sociology lecturing process. Amount of discussion about social interaction in sociology education is expected in Higher Education Level, namely social interaction between lecturers and students and between students and students. This study discusses about the role of lecturers in developing material to improve social interaction, developing verbal and written communication through communication media, the role of lecturers in developing sosial interaction at education sociology lecturing process. This study uses qualitative method. Data are collected by participatory observation, in-depth interviews and documentation techniques. Analysis techniques use data analysis in sites and cross sites. The results show that lecturers develop materials to improve student social interaction, lecturers develop verbal or written communication through discussions related to constraints students, and evaluating through paper assignments, journal making and directing students to the community.